(untitled) (Medical Forum Monthly, 2020)
Objective: To compare the outcome of harmonic Scalpel versus Conventional haemotasis in patients undergoing total thyroidectmy. Study Design: Randomized controlled comparative study. Place and Duration of Study: This study was conducted at the district head quarters & teaching Hospital Dera Ghazi Khan, from August 2019 to February 2020. Materials and Methods: Consective 94 patients undergoing thyroidectmy were taken and were divided into two groups. Group A were treated using harmonic scalpel and while there in group B were treated by conventional haemotasis by same surgeon to record outcomes. Both gender male and female patients were included and the age range of those patients were from 18-50 years. Patients having heart disease, CRF, CLD and with traumatic history and the patients with Hepatitis-B and Hepatitis-C and pregnant ladies were excluded from the study. Results: Of these 94 patients, 45(47.9%) were male patients while 49 (52.1%) were female patients. Mean age of patients was 37.26 + 5.50 years (with minimum age of study was 23 years while maximum age was 50 Years. Mean duration of surgery in group A was 41.94 + 5.82 minutes while in group B Mean duration was of surgery was 70.45 + 8.52 minutes (P = 0.000). Mean duration of hospital stay in group A was 2.74 + 0.675 days while in group B, it was 3.89 + 0.938 days (P = 0.000). hypocalcemia was noted in 29 (30.9 %) in group A hypocalcemia was noted to be 12.8 % versus 48.9 % in group B. (P = 0.000). Conclusion: Harmonic Scalpel is safe and effective procedure for patients undergoing total thyroidectmy as compared to Conventional haemostasis. Harmonic scalpel is associated with shorter duration of surgery, shorter hospital stay and decreased chance of Hypocalcemia.